Correlation between serum ferritin and gall stones - Patil, Girija; Srinivasan, Siddarth; Janakiraman, Sriram Prabhu Pandireddiyar (International Surgery Journal, 2020)
Background: The incidence of gall stones is in increasing trend. The old axiom that a typical gall stone sufferer is a fat, fertile, female of fifty, is only partially true, as the disease is found in women soon after their first delivery, in underweight and thin people. So, while searching for other parameters, iron deficiency was found to be a new parameter of interest in the aetiology of gall stones.7 Methods: 50 cases of cholelithiasis and 40 cases of anaemia with low serum ferritin levels from September 2017 to August 2019 was studied. Serum iron was estimated by carbonyl metallo-immunoassay method. Serum cholesterol was estimated by the CHOD-POD Enzymatic method. Biliary cholesterol was estimated after extraction of biliary lipids from bile from the gallbladder specimen of the patients by the method of Folch et al which was followed by the procedure similar to the analysis of serum cholesterol by CHOD-POD enzymatic method. Fischer’s chi square exact test was used as statistical method. Results: It was observed that 70% of the group A study group with cholelithiasis had normal serum ferritin levels and 30% had low serum ferritin levels. It was observed that 95% had normal sonographic findings and 5% had cholelithiasis with normal ferritin levels in group B. Conclusions: In our study low serum ferritin levels with cholelithiasis was associated with raised bile cholesterol levels and so it can be concluded that low serum ferritin level is causing biliary stasis and hence leading to increase in the incidence of cholelithiasis.